2022
DOI: 10.20473/mkh.v33i3.2022.233-243
|View full text |Cite
|
Sign up to set email alerts
|

Laporan Pertama Kasus Infestasi Spinturnix spp. pada Kelelawar Pemakan Buah (Rousettus spp.)

Abstract: Rousettus spp. is one of the wild animals that may transmit various diseases including zoonotic. Rousettus spp. or known as fruit bat is found in Java island and belongs to the Pteropodidae family. Generally, Rousettus spp. consumes fruit and floral products. This case report aims to detect ectoparasites in fruit bats (Rousettus spp.) found at Djawatan Banyuwangi, East Java. The samples in this case report are seven fruit bats (Rousettus spp.). Based on the results of laboratory identification using the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…mites on megabats from the genus Macroglossus and Rousettus (Fajri & Armiani 2021;Fajri et al 2018). Meanwhile, the study by Zania et al (2022) reported the Spinturnix mite infestation on Rousettus bats in Banyuwangi. This variation in findings suggested that the mites did not have a genus-specific pattern.…”
Section: Bat-ectoparasites Interactionmentioning
confidence: 99%
“…mites on megabats from the genus Macroglossus and Rousettus (Fajri & Armiani 2021;Fajri et al 2018). Meanwhile, the study by Zania et al (2022) reported the Spinturnix mite infestation on Rousettus bats in Banyuwangi. This variation in findings suggested that the mites did not have a genus-specific pattern.…”
Section: Bat-ectoparasites Interactionmentioning
confidence: 99%